2012
DOI: 10.1073/pnas.1119418109
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive kinase assay linked with phosphoproteomics for identifying direct kinase substrates

Abstract: Our understanding of the molecular control of many disease pathologies requires the identification of direct substrates targeted by specific protein kinases. Here we describe an integrated proteomic strategy, termed kinase assay linked with phosphoproteomics, which combines a sensitive kinase reaction with endogenous kinase-dependent phosphoproteomics to identify direct substrates of protein kinases. The unique in vitro kinase reaction is carried out in a highly efficient manner using a pool of peptides derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 43 publications
2
139
1
2
Order By: Relevance
“…Phosphorylation of Y354 on STIP1 has been characterized by a large-scale tyrosine phosphorylation study (51). This phosphorylation was also shown to be dependent on SYK in phosphoproteomic studies of MDA-MB-231 (41) and DG75 cells (28). Our in vitro kinase assay confirmed that Y354 was indeed the direct phosphorylation site of SYK.…”
Section: Validating Novel Syk Substrates In Vitro and In Vivo-supporting
confidence: 58%
See 4 more Smart Citations
“…Phosphorylation of Y354 on STIP1 has been characterized by a large-scale tyrosine phosphorylation study (51). This phosphorylation was also shown to be dependent on SYK in phosphoproteomic studies of MDA-MB-231 (41) and DG75 cells (28). Our in vitro kinase assay confirmed that Y354 was indeed the direct phosphorylation site of SYK.…”
Section: Validating Novel Syk Substrates In Vitro and In Vivo-supporting
confidence: 58%
“…Because in vitro kinase reactions typically display a degree of promiscuity (43), we further incorporated endogenous phosphoproteomic analysis from the previous study (28) using cells whose kinase of interest was either active or inhibited (Fig. 1, right panel).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations